DIVORCE AND PSYCHO - SOCIAL EFFECTS ON ADOLESCENTS IN ALBANIA - Mucaj, Arjana; Xeka, Shkelqim (European Scientific Journal, ESJ, 2015)
One of the biggest problems that societies are facing nowadays is divorce. Divorce can be considered a social wound, because it causes a huge emotional shock on adults and also to the children. In most of related cases divorce is caused by social problems like: unhappy marriages, sexual violence, psychological violence, crime etc. Divorce also acquires the status of being a social problembecause of the social problems it is related to. Concern remains that of children who come from divorced families who compared to other children, are more stressed. Their psychological traumatization goes in proportion with the degree of parental conflict during the process of divorce. In this study I have chosen to work with the teenagers manage and adapt to the process of divorce of their parents. Also I have studied the effects that leaves the process of divorce on adolescents and how teenagers cope with the difficulties of this process. However the thematic of the analysis will focus on how a number of factors affect the adaptation of adolescents with the divorce process. Firstly it is very important how adolescents perceive divorce. Secondly it is also very important the connection that they keep with their parents. Thirdly are economic difficulties that accompany divorce and fourthly remarriage of parents.